الإمام محمد بن عمر بن لبابة واختياراته الفقهية - ضيف محمد الصالح (University of Eloued جامعة الوادي, 2024)
يتناول هذا البحث الأثر الفقهي لأحد أعلام المدرسة المالكية الأندلسية، وهو الإمام أبو عبد الله محمد بن عمر بن لبابة (ت314)، حيث لم يحظ بدراسة كافية بالرغم من مكانته العلمية، وقد تناولت التعريف بحياته ووقفت على بعض اختياراته الفقهية التي خرج بها عن مشهور المذهب المالكي، وربّما إلى غيره من المذاهب الأخرى التي عرفتها الساحة الفقهية، وسجّلت حضورها في اختيارات بعض الفقهاء في ظلّ تمسّك الأندلسيين الشديد بالمذهب المالكي، ومع ذلك كلّه فقد عكست تلك الاختيارات والآراء الفقهية صورة التفاعل الإيجابي بين المذاهب الفقهية، والنزعة التحرّرية التي اختارها بعض الفقهاء منهجا للفتوى القضاء. - الكلمات المفتاحية: ابن لبابة، الاختيارات الفقهية، الفقه المالكي، المدرسة الأندلسية، منهج الفتوى. Abstract: This research tackles the jurisprudential impact of some scholars from the Andalusian and Maliki school. He is Alimam Abou Abdullah Mehammed Ben Omar Ben lebaba (d: 314), where he is not well studied despite his scientific position. I dealt with introducing his life I recognised his jurisprudential choices with which he departed from the well-known Maliki doctrine and probably to others from other doctrines known in the jurisprudential field and I recorded its presence in some jurists choices during the Andalusians strong adherence to the Maliki doctrine. Despite of all that, those choices and jurisprudential views reflected the image of the positive interaction between the jurisprudential doctrines and the libertarian tendancy chosen by some jurists as an approach for the judicial fatwa. key words: Ibn lebaba; jurisprudential choices; Maliki jurisprudence; Andalusian school; Fatwa Methodology
Keywords: ابن لبابة; الاختيارات الفقهية; الفقه المالكي; المدرسة الأندلسية; منهج الفتوى; Ibn Lubaba; Jurisprudential Choices; Maliki Jurisprudence; Andalusian School; Methodology of Fatwa